Efficiency, productivity and Islamic banks: an application of DEA and Malmquist index. Issue 1 (9th February 2015) - Abbas, Muhammad; Hammad, Rayan S; Elshahat, Mohamed Fathy; Azid, Toseef
Abstract : Purpose: – This paper aims to compute the Malmquist Index of Islamic and conventional banks to compare their performance in the sample period of 2005-2009. Islamic banks have been showing tremendous growth throughout the world in recent past. Their progress is exceptional in Islamic countries on account of patronization for religious reasons. There existed vacuum in research of their productivity change over the years. Design/methodology/approach: – This study tries to apply the Malmquist Index. The Malmquist Total Factor Productivity Index has been further divided into Efficiency Change Index, Technological Change Index, Pure Efficiency Change Index and Scale Efficiency Change Index to obtain an insight about the reasons for the change in productivity. Findings: – Results indicate that the productivity of Islamic banks decreased in 2007 but it increased in 2008 to 2009. Islamic banks had higher productivity growth from 2005 to 2006, but they experienced lower growth in subsequent years as compared to their conventional counterparts. Research limitations/implications: – Data were not available before 2005 in Pakistan. Practical implications: – This study is helpful for the investors and bankers for formulating the future policy. Social implications: – This study also provides a guideline for establishing the ethical financial institutions. Originality/value: – This is an original attempt.